174k views
0 votes
Which expression is equivalent to √-108 - √-3

User Anuraj
by
6.1k points

2 Answers

3 votes
6sqrt3 = sqrt(36*3) = sqrt108

so choice B is right sure

hope helped
User Bitclef
by
6.3k points
6 votes

Answer:

The equivalent expression will be
5i√(3)

Explanation:

The given expression is:
√(-108)-√(-3)


√(-108)-√(-3)\\ \\ =√(36*(-3))-√(-3)\\ \\ =√(36)*√(-3)-√(-3)\\ \\ =6√(-3)-√(-3)\\ \\ =5√(-3)\\ \\ =5i√(3)

[As
i= √(-1)]

So, the equivalent expression will be
5i√(3)

User GottZ
by
6.7k points